Notch Signaling Pathway Expression in the Skin of Leprosy Patients: Association With Skin and Neural Damage (2020)
ABSTRACT: Leprosy is an infectious disease caused by Mycobacterium leprae, a debilitating disease that affects the skin and peripheral nerves. It is possible that tissue changes during infection with leprosy are related to alterations in the activity of the Notch signaling pathway, an innate signaling pathway in the physiology of the skin and peripheral nerves. Methods: This is a descriptive observational study. Thirty skin biopsies from leprosy patients and 15 from individuals with no history of this disease were evaluated. In these samples, gene expressions of cellular components associated with the Notch signaling pathway, Hes-1, Hey-1, Runx-1 Jagged-1, Notch-1, and Numb, were evaluated using q-PCR, and protein expression was evaluated using immunohistochemistry of Runx-1 and Hes-1. Results: Changes were observed in the transcription of Notch signaling pathway components; Hes-1 was downregulated and Runx-1 upregulated in the skin of infected patients. These results were confirmed by immunohistochemistry, where reduction of Hes-1 expression was found in the epidermis, eccrine glands, and hair follicles. Increased expression of Runx-1 was found in inflammatory cells in the dermis of infected patients; however, it is not related to tissue changes. With these results, a multivariate analysis was performed to determine the causes of transcription factor Hes-1 reduction. It was concluded that tissue inflammation was the main cause. Conclusions: The tissue changes found in the skin of infected patients could be associated with a reduction in the expression of Hes-1, a situation that would promote the survival and proliferation of M. leprae in this tissue.